QUANTITATIVE ESTIMATION OF SOME METABOLITES AND ENZYMES IN INSECT INDUCED LEAF GALLS OF FICUS RELIGIOSA: Life Science-Plant Pathology - PRAKASH MEENA, VIJAY; CHAND MEENA, MAHESH; LATA SHARMA, SUMAN (International Journal of Life Science and Pharma Research, 2014)
This Paper reports the quantitative estimation of some metabolites and enzymes in insect induced leaf galls of Ficus religiosa. The parameters assayed were total soluble sugar, reducing sugar, starch a-amylase activity and invertase activity compared to normal tissues. Galls showed significantly higher content of total soluble sugar, reducing sugar, starch a-amylase activity and invertase enzymes activity and lower content of reducing sugar.